2018
DOI: 10.31219/osf.io/ztw9j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Control and the Reasons Behind Our Goals

Abstract: Motivation derived from a sense of truly valuing or enjoying one’s pursuits (“wanting to do it”) – as opposed to motivation born of external demands or other people’s expectations (“having to do it”) – is associated with goal-pursuit success and overall well-being. But what determines the quality of motivation in the first place? Many theoretical perspectives identify features of the task or situation as determinants, but have largely ignored the potential contribution of individual self-regulatory tendencies.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…People differ in their strength of need for autonomy (Prentice, Halusic, & Sheldon, ) and also in the frequency with which they experience autonomy on daily basis. However, not much is known about correlates of these individual differences (Converse et al, ). The results of our current study indicate links between the frequency of experience of autonomy in everyday behaviours and general personality dispositions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People differ in their strength of need for autonomy (Prentice, Halusic, & Sheldon, ) and also in the frequency with which they experience autonomy on daily basis. However, not much is known about correlates of these individual differences (Converse et al, ). The results of our current study indicate links between the frequency of experience of autonomy in everyday behaviours and general personality dispositions.…”
Section: Discussionmentioning
confidence: 99%
“…Ching et al () showed, however, that perceived autonomy in daily situations does not moderate the strength of the relationships between personality traits and states. On the other hand, Converse, Juarez, and Hennecke () suggested that perceived autonomy can be of interest as a dependent variable. They noted that the potential contribution of individual differences to the quality of motivation has been ignored thus far by both theory and research.…”
mentioning
confidence: 99%
“…Recent evidence suggest that self‐control relates to a broad range of behaviours and processes beyond the effortful inhibition of undesired responses: for example, it has been associated with the proactive avoidance of temptation (Ent, Baumeister, & Tice, ), the establishment of beneficial habits (Adriaanse, Kroese, Gillebaart, & De Ridder, ; Galla & Duckworth, ), the experience of one's daily activities as more autonomously regulated (e.g. more fun and interesting; Converse, Juarez, & Hennecke, ), and a weakened desire for temptations that conflict with a current goal (Hofmann, Baumeister, Förster, & Vohs, ). We locate our approach within this broad view of trait self‐control as reflecting a group of processes that determine how people pursue goals in different situations (Fleeson & Jayawickreme, ; McCabe & Fleeson, ).…”
Section: Self‐regulatory Strategiesmentioning
confidence: 99%
“…Such motivation is thought to be judged by integrating information about the broader goal (e.g., am I performing this action in service of a want‐to or have‐to goal? ), relevant contextual cues (e.g., how interesting is this activity; Sansone & Thoman, ), and individual differences (e.g., trait self‐control; Converse Juarez, & Hennecke, ).…”
Section: Goal Motivation: Pursuing Goals Because You Want‐to Vs Have‐tomentioning
confidence: 99%